DESIGN OF THE STRUCTRUCAL OF FLYOVER PADALARANG WITH PCU GIRDER - Diktriany, Shenny
Population growth in West Bandung Regency continues to increase, followed by growth in vehicle traffic, causing congestion problems at several points. One of them is Simpang Padalarang, whose performance condition is getting worse. To improve traffic mobility and better intersection performance, it is necessary to build a flyover that connects Kota Baru Parahyangan with the Purbaleunyi toll gate. The Padalarang flyover is designed to have a width of 24.24 m and total length of 292 m, with 6 bridge spans supported by 5 pillars and 2 abutments. This final project discusses the design of the Padalarang Flyover structure which consists of abutments, pillars, girders, diaphragms, and slabs. The process of analyzing the bridge structure against the design loads is carried out by 3D analysis using Midas Civil software. The design of pillar columns and abutment walls is also assisted by SpCol software. The bridge girder was designed using prestressed concrete U-girders, PCU H-185 for a bridge span of 35 m and PCU H-165 for a bridge span of 30 m. The girder rests on elastomeric bearings over a abutment type wall and pillar with 2 columns. Planning is also carried out in the field of construction management including construction implementation methods, budget planning, and scheduling.